Iron-containing flux prepared from red mud and use thereof
Patent Information
- Application Number
- CN202611066755.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-17
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2046-07-17
AI Technical Summary
[0007]综上所述,现有技术虽从不同角度对赤泥资源化进行了探索,但仍存在以下关键问题:(1)赤泥直接用于烧结时未进行有害组分预处理,导致钠、铝进入冶炼体系并产生不利影响;(2)现有脱碱技术未充分考虑处理后产物中铝组分的赋存状态对后续烧结行为的影响;(3)尚未形成一种在温和条件下实现赤泥深度脱钠与铝组分矿相重构,并将其作为烧结熔剂高比例利用的一体化技术路径
[0041]1.本发明通过水热矿相重构,将赤泥中对烧结有害的活性含铝物相(如勃姆石、方钠石中的活性Al组分)一部分溶出,并一部分转化为具有高温稳定性的钙铝硅酸盐晶相(钙铝黄长石(Ca2Al2SiO7)、水化石榴石(Ca3Al2(SiO4)3)和/或水化铝酸三钙(C3AH6))及其同类结构物相。铝组分被牢固地固定在晶体结构中,在1250~1350℃的烧结温度区间内不会分解释放活性Al2O3,从而从根源上避免了活性Al2O3对CaO的竞争消耗,使得CaO主要用于生成铁酸钙(SFCA)粘结相。
Smart Images

Figure CN122564260B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of metallurgical solid waste resource utilization technology, specifically relating to an iron-containing flux prepared from red mud and its application. Background Technology
[0002] Red mud is a solid waste generated during alumina production. It has a complex composition and is highly alkaline, mainly containing various oxides such as Fe2O3, Al2O3, SiO2, CaO, Na2O, and TiO2. It may also contain heavy metal ions and radioactive elements. Some red mud may be managed as Class II general industrial solid waste due to the high alkalinity of its leachate and high pollutant levels. Currently, a large amount of red mud is still disposed of through open-air damming and stockpiling, which not only occupies a significant amount of land resources but also poses environmental risks such as alkaline leakage and heavy metal migration, causing continuous impacts on soil, groundwater, and the ecological environment. This has become a key issue restricting the green development of the alumina industry. Therefore, achieving large-scale, resource-based utilization of red mud is of great significance.
[0003] Red mud contains a certain amount of iron, especially some high-iron red mud or red mud concentrate obtained after iron beneficiation, whose total iron content can reach 35% to 55%, possessing potential value as a raw material for ironmaking. However, this type of material still contains high levels of sodium and aluminum, which will have significant adverse effects if used directly in ironmaking: sodium is prone to enrichment and circulation in the blast furnace, leading to problems such as deterioration of furnace charge permeability, blast furnace nodule formation, and furnace lining erosion; aluminum will increase the viscosity of the sintering liquid phase, reduce the mineral assimilation capacity, thereby leading to a decrease in sinter strength and deterioration of reduction performance.
[0004] In terms of red mud resource utilization, existing technologies mainly include multi-component recovery (e.g., patent applications CN116040666A and CN101538058A), zeolite preparation (e.g., patent application CN113716583A), building material utilization (e.g., patent application CN109020459A), and metallurgical process disposal, among other pathways. While building material utilization and functional material preparation can achieve localized high-value utilization of red mud, their disposal capacity is limited by market size and process scale, making it difficult to meet the processing needs of red mud production reaching hundreds of millions of tons annually. Metal recovery technology, although capable of extracting iron resources from red mud, typically requires high-temperature treatment, resulting in high energy consumption, complex processes, and high costs, hindering large-scale promotion. In contrast, the iron and steel smelting process, especially sintering and pelletizing, features large raw material processing capacity, strong raw material adaptability, and the ability to synergistically dispose of various iron-containing solid wastes, making it one of the few industrial pathways currently capable of achieving large-scale red mud utilization.
[0005] Extensive research has been conducted on the resource utilization of red mud in sintering systems. Existing technologies propose introducing red mud as an iron-containing raw material or auxiliary material into the sintering process. For example, red mud can be mixed with fuel, recycled ore, etc., granulated, and then added to the sintering process, or the binding properties of red mud can be used to partially replace bentonite in the preparation of sinter. However, none of these methods effectively pre-treat the sodium and active aluminum-containing components in the red mud, which still adversely affect the process and product performance after entering the sintering system. For example, high sodium content increases the alkali load of the blast furnace, while high aluminum content deteriorates the mineral structure and metallurgical properties of the sinter, thus limiting the proportion of red mud added or its application range.
[0006] To mitigate the impact of harmful components such as sodium in red mud, some technologies propose pre-treatment with dealkali removal. For example, sodium can be removed by adding calcium oxide during the red mud washing process, or a calcification dealkali removal process (such as patent CN115028180A) can be used to reduce the Na₂O content in the red mud. While these methods can reduce the sodium content in red mud to some extent, they do not adequately address the occurrence state of aluminum components in the red mud. Under conventional calcification dealkali removal conditions, the aluminum-containing phases in the raw material may remain active and will still react with CaO during subsequent high-temperature processes, affecting the mineral structure of the sinter. Furthermore, existing dealkali removal technologies primarily use the treated red mud for direct reduction or building materials applications, failing to effectively integrate it with the sintering and ironmaking process.
[0007] In summary, although existing technologies have explored the resource utilization of red mud from different perspectives, the following key issues still exist: (1) When red mud is directly used for sintering, harmful components are not pretreated, leading to sodium and aluminum entering the smelting system and causing adverse effects; (2) Existing dealkali removal technologies do not fully consider the influence of the occurrence state of aluminum components in the treated product on subsequent sintering behavior; (3) An integrated technical path has not yet been formed to achieve deep sodium removal and aluminum component mineral phase reconstruction of red mud under mild conditions, and to utilize it as a sintering flux in a high proportion. Therefore, developing a conditioning method that can transform the aluminum-containing phase in red mud into a specific crystal phase structure, thereby improving its applicability as a sintering raw material, is of great significance for realizing the large-scale, high-value utilization of red mud in the sintering process. Summary of the Invention
[0008] The purpose of this invention is to overcome the shortcomings of existing technologies and provide an iron-containing flux prepared from red mud and its application. This invention addresses the issue of red mud undergoing hydrothermal conditioning treatment to achieve deep sodium removal while simultaneously transforming the aluminum-containing phase in the raw material into a calcium aluminum silicate crystal phase with a specific crystal structure. The resulting reconstituted product is then used as an iron-containing calcium flux in sintering production, replacing a portion of traditional flux by equivalent CaO content, thereby achieving large-scale synergistic utilization of red mud in the iron and steel smelting process.
[0009] The key to this invention lies in the hydrothermal mineral phase reconstruction, which allows the active aluminum-containing phases in the raw materials (such as the active Al components in boehmite and sodalite) to dissolve and transform into structurally stable calcium aluminum silicate crystal phases. During subsequent sintering, the aluminum components in these crystal phases are stably fixed within the crystal structure and do not compete with CaO for reaction; while the calcium components undergo inconsistent melting and are gradually released within the 1100–1300°C range. The timing of this release closely matches the formation temperature range of calcium ferrite (SFCA), thus achieving synergistic regulation of "aluminum stabilization and controllable calcium release."
[0010] To achieve the above objectives, the present invention adopts the following technical solution:
[0011] This invention discloses an iron-containing flux prepared from red mud, which is prepared through the following steps:
[0012] Step 1: Raw material preparation: Select iron-containing red mud or red mud iron concentrate as raw material; preferably, the particle size of the raw material is 80-200 mesh. More preferably, the raw material is ground so that 100% passes through a 100-mesh sieve (particle size ≤150μm).
[0013] Step 2: Hydrothermal mineral phase reconstruction: The raw materials are mixed with a calcium-containing conditioning agent and water to form a slurry. The slurry is then subjected to a mineral phase reconstruction reaction under hydrothermal conditions. The calcium-containing conditioning agent is calcium oxide and / or calcium hydroxide. The hydrothermal treatment conditions are: temperature 150-200℃, time 1-7h, liquid-to-solid ratio 3-12mL / g, and the molar ratio of Ca element in the conditioning agent to the sum of Al and Si elements in the raw materials (Ca / (Al+Si)) is 0.6-1.1. After the reaction, the reconstructed product is obtained by solid-liquid separation. When the hydrothermal liquid-to-solid ratio is lower than 3mL / g, the slurry has poor fluidity and the reaction is uneven; when it is higher than 12mL / g, the liquid phase volume is too large, which will increase the load on subsequent processing. The reconstructed product is an iron-containing flux, which meets the following characteristics: (a) Na2O content is not higher than 0.5wt%; (b) TFe is not less than 50wt% and CaO content is 5-12wt%; (c) Al2O3 content is 3-8wt%; (d) In the X-ray diffraction (XRD) pattern of the iron-containing flux, characteristic diffraction peaks of calcium aluminum silicate crystal phase belonging to the CaO-Al2O3-SiO2 system appear, and there are no characteristic diffraction peaks of sodalite group minerals, no characteristic diffraction peaks of boehmite, and no characteristic diffraction peaks of aluminum hydroxide phase.
[0014] In step 2, the amount of conditioning agent is controlled using the Ca / (Al+Si) molar ratio instead of the traditional Ca / Si molar ratio. This has the advantage that the Ca / (Al+Si) molar ratio can simultaneously reflect the reaction matching relationship between the calcium source and the two key components, aluminum and silicon. It more accurately characterizes the amount of calcium required to generate the calcium aluminum silicate crystal phase during the hydrothermal mineral phase reconstruction process, avoiding insufficient or excessive calcium source due to large fluctuations in the Al2O3 content in the raw materials. This makes the formation of the target crystal phase and the removal of sodium more stable and controllable. Furthermore, the Ca / (Al+Si) molar ratio defined in this invention refers to the ratio of the molar amount of Ca in the added calcium-containing conditioning agent to the molar amount of (Al+Si) in the raw materials.
[0015] Preferably, the temperature of the hydrothermal treatment in step 2 is 170–190°C, the time is 2–5 h, and the liquid-to-solid ratio is 5–10 mL / g.
[0016] Preferably, when calcium oxide is selected as the calcium-containing conditioning agent, the hydrothermal treatment conditions are as follows: preferably, the temperature is 170-190℃, the time is 2-5h, the liquid-to-solid ratio is 5-9mL / g, and the molar ratio of Ca element in the conditioning agent to the sum of Al and Si elements in the raw material, Ca / (Al+Si), is 0.8-1.0.
[0017] Preferably, when calcium hydroxide is used as the calcium-containing conditioning agent, its solubility in water is lower than that of calcium oxide. Within the acceptable range, the liquid-to-solid ratio can be appropriately increased or the reaction time extended to ensure that the conditioning agent is fully dissolved and participates in the reaction. This demonstrates the good adaptability of the technical solution of this invention to different types of calcium-containing conditioning agents. Specifically, the hydrothermal treatment conditions are: temperature 170-190℃, time 3-6h, liquid-to-solid ratio 8-10mL / g, and the molar ratio of Ca element in the conditioning agent to the sum of Al and Si elements in the raw material, Ca / (Al+Si), is 0.8-1.0.
[0018] Preferably, in step 2, by controlling the Ca / (Al+Si) molar ratio to be 0.8 to 1.0, an aluminum-containing phase, mainly in the form of calcium aluminum silicate crystals, is generated in the product.
[0019] Preferably, the raw materials in step 1 have a TFe content of 30-55 wt%, more preferably 40-55 wt%, a Na2O content of ≥1 wt%, more preferably 1-5.5 wt%, an Al2O3 content of 4-20 wt%, and a SiO2 content of 0.5-20 wt%.
[0020] Preferably, after solid-liquid separation in step 2, the obtained solid phase is washed, preferably by countercurrent washing, with a liquid-to-solid ratio of 3 to 10 mL / g and 2 to 3 washes.
[0021] Preferably, after the hydrothermal mineral phase reconstruction is completed, the sodium removal rate is not less than 85%, and more preferably not less than 90%.
[0022] Preferably, after the hydrothermal mineral phase reconstruction is completed, the aluminum removal rate is not less than 40%, more preferably not less than 50%.
[0023] Preferably, the X-ray diffraction pattern of the iron-containing flux shows characteristic diffraction peaks of calcium aluminum silicate crystal phases belonging to the CaO-Al2O3-SiO2 system. The crystal phases include one or more of calcium aluminum feldspar (Ca2Al2SiO7), hydrated garnet (Ca3Al2(SiO4)3), and / or tricalcium aluminate hydrate (C3AH6), and can be further extended to one or more of the calcium aluminum feldspar group, hydrated garnet group, dicalcium aluminate hydrate, calcium aluminate hydrate, and similar aluminum-containing phases with similar calcium-aluminum-silicon or calcium-aluminum structures. At the same time, the characteristic diffraction peaks of sodalite group minerals in the raw material disappear, and the broad diffuse peaks or weak diffraction peaks of boehmite or aluminum hydroxide phases in the raw material disappear.
[0024] In addition, a small amount of calcium carbonate may be generated in the iron-containing flux. This invention does not target the andradite-type phase as the reconstructed phase, but preferably allows aluminum to exist primarily as a calcium aluminum silicate crystalline phase. When a small amount of andradite-type or similar secondary phases are present in the reconstructed product, their content should be such that it does not affect the sodium removal effect, the controllable release characteristics of calcium, or the sintering application performance of the reconstructed product. This is because the andradite-type phase is usually more easily generated under conditions of excessive calcium source or strong calcification. Its crystal structure may simultaneously solidify components such as Ca, Fe, and Al, reducing the releaseability of some calcium during sintering and potentially forming an inert phase with a higher melting point and greater difficulty in assimilation. If the content of this type of phase is too high (e.g., greater than or equal to 5 wt% according to XRD semi-quantitative analysis), it may weaken the synergistic effect of "aluminum stabilization and controllable calcium release" in this invention, and reduce the iron mineral assimilation capacity and the amount of calcium ferrite (SFCA) binder phase generated. Therefore, by controlling the Ca / (Al+Si) molar ratio, hydrothermal temperature, and reaction time, this invention enables aluminum to be mainly converted into calcium aluminum silicate crystalline phases and suppresses the large-scale formation of hedophilic garnet phases, thereby improving the applicability of the reconstructed product as a sintering iron-containing calcium flux.
[0025] The iron-containing flux obtained in this invention contains iron in the following states: hematite (Fe2O3), goethite and / or ferrihydrite, etc., as well as one or more of iron spinel phases; wherein, iron mainly exists in the form of iron oxide or iron hydroxyl oxide.
[0026] During the hydrothermal conditioning process, soluble sodium and some aluminum components enter the liquid phase, while the remaining aluminum components react with calcium and silicon components to form a calcium aluminum silicate crystal phase with a well-defined crystalline structure. The resulting liquid phase is rich in sodium and aluminum and can be recycled for subsequent batches of hydrothermal conditioning, i.e., leaching new red mud with the leachate, achieving multiple recycling of the liquid phase. When the Na in the circulating liquid phase... + When the concentration reaches 30-40 g / L, the sodium salt and aluminum resources are separated and recovered in a unified manner, thereby significantly reducing wastewater discharge and improving the recovery efficiency of valuable components.
[0027] This invention relates to the application of an iron-containing flux prepared from red mud as raw material, comprising adding the obtained iron-containing flux (i.e., the reconstituted product of this invention) as an iron-containing calcium flux to ironmaking raw materials, mixing them evenly to obtain a sintering mixture; the proportion of iron-containing flux added to the sintering mixture is 5-20 wt%; based on the CaO content in the iron-containing flux, it replaces the CaO provided by limestone and / or quicklime in the sintering mixture in an equal amount, and by adjusting the batching to ensure that the basicity (CaO / SiO2) of the sintering mixture remains unchanged in the range of 1.8-2.2, and using the sintering process to prepare ironmaking furnace charge.
[0028] The sintering mixture has a moisture content of 6.5–8.0 wt%.
[0029] After the sintering mixture is added to the sintering furnace, it is ignited at 1050–1180°C, followed by sintering. During sintering, the negative pressure of the exhaust fan is controlled at 8–15 kPa, and the sintering temperature is 1250–1350°C, preferably 1280–1320°C. The above sintering temperature refers to the measured temperature range of the combustion zone or high-temperature reaction zone during sintering, not the set temperature of the ignition furnace. This temperature range can meet the requirements for liquid phase generation and calcium ferrite (SFCA) formation, while avoiding local overmelting that would reduce permeability.
[0030] The sintering mixture comprises iron ore (iron-containing raw material), iron-containing flux (i.e., the reconstructed product of this invention), limestone, quicklime, dolomite, fuel (coke powder), and recycled ore. The components, by dry basis mass percentage, range as follows: iron ore 50–75%, iron-containing flux 5–12%, limestone 2–10%, quicklime 0–10%, dolomite 0–8%, coke powder 3–8%, and recycled ore 5–15%; the sum of the contents of all components is 100%.
[0031] When the iron-containing flux obtained in this invention is used in sintering, it is necessary to control the main processes and parameters:
[0032] (1) Moisture control of the mixture: The moisture content of the mixture should be controlled at 6.5-8.0 wt% (preferably 7.0-7.5 wt%). Too low moisture content will lead to poor granulation effect of the mixture, deterioration of the permeability of the material layer, poor heat transfer during sintering, insufficient liquid phase generation, and a decrease in the strength of the sintered ore; too high moisture content will cause excessive heat absorption by water evaporation in the material layer, increasing heat loss, and at the same time, the excessively wet layer will thicken during the sintering process, which will also worsen the permeability. Appropriate moisture content can promote pelleting of the mixture, improve the permeability of the material layer, and ensure the smooth operation of the sintering process.
[0033] (2) Ignition temperature control: The ignition temperature should be controlled at 1050~1180℃ (preferably 1100~1150℃), and the ignition time should be 1.5~3min. If the ignition temperature is too low, the surface mixture will not be able to obtain enough heat to complete the sintering reaction, resulting in raw material; if the ignition temperature is too high, the surface sinter will be over-melted, affecting the quality of the surface sinter and increasing energy consumption.
[0034] (3) Control of negative pressure of exhaust: The negative pressure of exhaust should be controlled at 8 to 15 kPa. When the negative pressure is too low, the air volume through the material layer is insufficient, the combustion zone moves downward slowly, and the sintering speed is reduced; when the negative pressure is too high, the material layer will be too tight, the airflow resistance will increase, and fine particles will be easily drawn away, resulting in an increase in dust removal load.
[0035] (4) Basicity control: The basicity (CaO / SiO2) of sinter should be controlled between 1.8 and 2.2. When the basicity is too low, the amount of liquid phase in sintering is insufficient and the strength of sinter is poor; when the basicity is too high, too many high-melting-point phases will be generated, which will deteriorate the low-temperature reduction pulverization performance of sinter.
[0036] In this invention, the iron ore is a commonly used iron-containing raw material in sintering production, including fine powder, concentrate powder, lump ore undersize powder, and mixtures of two or more thereof; based on dry basis mass percentage, the main components of the iron ore range as follows: TFe content is 55-68 wt%, SiO2 content is 2-10 wt%, Al2O3 content is 0.5-5 wt%, CaO content is 0-8 wt%, MgO content is 0-5 wt%, FeO content is 0-10 wt%, loss on ignition is 0-12 wt%, S is not higher than 0.15 wt%, and P is not higher than 0.20 wt%.
[0037] In this invention, the returned ore refers to the finer particle size (i.e., particle size less than 5 mm) portion of the sintered ore that has been crushed and screened and then returned to the sintering batching system.
[0038] Based on dry weight percentage, the main components of the returned ore include: TFe content of 50–62 wt%, FeO content of 5–15 wt%, SiO2 content of 4–9 wt%, Al2O3 content of 1–5 wt%, CaO content of 8–16 wt%, MgO content of 1–5 wt%, loss on ignition of 0–5 wt%, S not exceeding 0.15 wt%, and P not exceeding 0.20 wt%; the basicity of the returned ore, CaO / SiO2, is preferably 1.6–2.5.
[0039] Beneficial effects
[0040] Compared with the prior art, the present invention has the following beneficial effects:
[0041] 1. This invention utilizes hydrothermal mineral phase reconstruction to dissolve a portion of the active aluminum-containing phases in red mud that are detrimental to sintering (such as the active Al components in boehmite and sodalite), and transform a portion into high-temperature stable calcium aluminum silicate crystal phases (calcium aluminum feldspar (Ca2Al2SiO7), hydrated garnet (Ca3Al2(SiO4)3), and / or hydrated tricalcium aluminate (C3AH6)) and similar structural phases. The aluminum components are firmly fixed in the crystal structure and will not decompose and release active Al2O3 within the sintering temperature range of 1250–1350℃. This fundamentally avoids the competitive consumption of CaO by active Al2O3, allowing CaO to primarily be used to generate the calcium ferrite (SFCA) binder phase.
[0042] 2. In the reconstructed product obtained by this invention, calcium exists in the form of calcium aluminum silicate crystalline phase. During the subsequent sintering process at 1250–1350°C, the above-mentioned crystalline phase undergoes inconsistent melting, and the calcium component is released in a controlled manner. The release temperature highly matches the formation temperature range of calcium ferrite (SFCA); while the aluminum component remains fixed in the residual solid phase due to the stability of the Si-O-Al framework. The "slow-release calcium supply" characteristic of the reconstructed product of this invention makes the release timing of CaO more coordinated with the redox reaction of hematite and the formation kinetics of SFCA, thereby improving the effective utilization rate of CaO and reducing the ineffective consumption of calcium source in the preheating zone.
[0043] 3. The reconstructed product of this invention has the dual functions of iron source and flux. For raw materials with different iron grades (TFe 38%~52%), the TFe content of the reconstructed product after treatment is increased to over 50%, and the CaO content reaches 5~12wt%. When replacing part of the limestone and / or quicklime flux with CaO equivalent, iron content can be supplemented at the same time, avoiding the dilution problem of sinter grade caused by the endothermic decomposition of carbonates and the introduction of iron-free gangue in traditional limestone flux.
[0044] 4. The method of this invention has mild process conditions (150-200℃), requires no high-temperature roasting, and has a simple process flow. The resulting reconstituted product can be directly applied to the sintering process at a ratio of 5-20%. The drum strength, yield, reduction degree, and low-temperature reduction pulverization rate of the obtained sinter all meet the requirements of blast furnace ironmaking, providing a technically and economically feasible path for the large-scale utilization of high-iron red mud. Simultaneously, this invention avoids the formation of obvious calcium-iron garnet-type phases, allowing added calcium to preferentially enter the target calcium-aluminate silicate crystalline phase and achieve controlled release within the high-temperature range of sintering. This prevents calcium, iron, and aluminum from being excessively consolidated in the refractory inert phase, thereby improving the assimilation capacity of iron minerals and the formation efficiency of the SFCA binder phase, and improving the strength and metallurgical properties of the sinter. Attached Figure Description
[0045] Figure 1 This is a schematic diagram of the process flow of the method described in this invention.
[0046] Figure 2 The X-ray diffraction (XRD) pattern of the raw materials used in Example 1.
[0047] Figure 3 The image shows the X-ray diffraction (XRD) pattern of the reconstructed product obtained in Example 1.
[0048] Figure 4 The X-ray diffraction (XRD) pattern of the raw materials used in Example 2. Detailed Implementation
[0049] To better understand the present invention, it will be described in further detail below with reference to embodiments and comparative examples. It should be noted that the following embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention.
[0050] Example 1
[0051] Step 1: Raw material preparation; The iron-containing red mud used in this embodiment is high-iron red mud discharged during the Bayer process of an alumina plant. Its chemical composition analysis results are shown in Table 1. The total iron content of this high-iron red mud is 40.1 wt%, the Na2O content is 3.5 wt%, and the Al2O3 content is 14.9 wt%.
[0052] Table 1. Main chemical composition of high-speed iron red mud (wt%)
[0053] X-ray diffraction analysis was performed on the above-mentioned high-iron red mud raw material, and the XRD pattern is shown below. Figure 2 As shown, the main phases in this raw material include: (1) hematite (Fe2O3), which has sharp characteristic diffraction peaks and is the main iron-containing phase in the raw material; (2) sodalite group minerals (Na 7.5Al6(SiO4)6(OH) 1.5 (H2O)5 or similar composition), is one of the main carriers of Na and Al in the raw material; (3) Boehmite (AlO(OH)), some of its diffraction peaks overlap with the peaks of sodalite group minerals; (4) Quartz (SiO2); (5) Goethite (FeO(OH)). This raw material has a high degree of crystallinity, sodium is mainly found in sodalite group minerals, while aluminum is found in both sodalite group minerals and boehmite.
[0054] Step 2: Hydrothermal mineral phase reconstruction; Take the above-mentioned high-iron red mud (100% passing through a 100-mesh sieve), add calcium oxide (CaO) as a calcium-containing conditioning agent, and control the molar ratio of Ca element in the conditioning agent to the sum of Al and Si elements in the raw material, Ca / (Al+Si), to be 1.0. Add deionized water to adjust the liquid-solid ratio to 8 mL / g, and stir evenly to prepare a slurry. Put the slurry into a hydrothermal reactor and react at 180℃ for 3 h. After the reaction, the reaction product is subjected to solid-liquid separation. The obtained solid phase is washed twice by countercurrent washing, with a liquid-solid ratio of washing water to solid phase of 5 mL / g. After washing, dry at 105℃ for 12 h to obtain the reconstructed product.
[0055] The chemical composition of the obtained reconstructed product was analyzed, and the results are shown in Table 2.
[0056] Table 2. Main chemical composition of the reconstituted products (wt%)
[0057] As shown in Table 2, after hydrothermal mineral phase reconstruction treatment, the Na2O content in the reconstructed product decreased from 3.52wt% to 0.23wt%, and the sodium removal rate reached 93.5%; the total iron content increased from 40.12wt% to 51.5wt%; and the CaO content reached 8.3wt%.
[0058] The obtained reconstructed product was subjected to X-ray diffraction analysis, and the XRD pattern is shown below. Figure 3 As shown. (Compared to the raw material spectrum) Figure 2 In comparison, the phase composition of the reconstructed product changed significantly: (1) the characteristic diffraction peaks of sodalite group minerals in the raw material disappeared in the spectrum of the reconstructed product, the crystal structure of sodalite group minerals was destroyed, and sodium ions dissolved from the lattice and entered the liquid phase; (2) the diffraction peaks of boehmite in the raw material disappeared in the spectrum of the reconstructed product, and at the same time, hydrated garnet (Ca3Al2(SiO4)) appeared in the reconstructed product. 0.6 (OH) 9.6 (3) The diffraction peaks of hematite and goethite still exist and their intensity is enhanced, which is consistent with the result of iron grade improvement. (4) A small amount of calcium carbonate diffraction peaks also appear in the product, and no diffraction peaks corresponding to andradite are found.
[0059] Step 3: Sintering utilization; The reconstructed product obtained in Step 2 is used as an iron-containing calcium flux and added to the sintering mixture at a mass ratio of 8%. At the same time, the CaO content in the reconstructed product is converted to replace the CaO provided by limestone in the sintering mixture in an equal amount. The basicity of the sintering mixture is kept constant by adjusting the batching. The specific proportion of the sintering mixture is shown in Table 3.
[0060] Table 3. Sintering Mix Proportion Table (dry basis, wt%)
[0061] The composition of the iron ore in Table 3 is as follows: TFe: 62.3wt%, SiO2: 5.1wt%, Al2O3: 2.0wt%, CaO: 1.1wt%, MgO: 1.4wt%, FeO: 3.8wt%, loss on ignition: 5.5wt%, S: 0.04wt%, P: 0.08wt%.
[0062] The basicity (CaO / SiO2) of the sintering mixture was controlled at 2.0, and the moisture content was 8.0%. Sintering tests were conducted according to the following parameters: the sintering mixture was loaded into the sintering furnace, the ignition temperature was 1150℃, the ignition time was 90s, the suction negative pressure was 15kPa, the highest temperature of the combustion zone in the material layer during sintering was approximately 1260℃, and natural cooling was performed after sintering. The resulting sinter was tested for performance: drum strength was 63.8%, yield was 76.2%, reducibility (RI) was 86.5%, and low-temperature reduction pulverization rate (RDI) was [not specified]. +3.15 The figure was 72.1%.
[0063] The calculation of the sintering yield is explained as follows: After the sintering test, the obtained sintered ore was crushed by a single-roll crusher and then sieved sequentially through 40mm, 25mm, 16mm, 10mm, and 5mm sieves. The mass of sintered ore with a particle size greater than 5mm after sieving was taken as the mass of the finished sintered ore. The yield was calculated using the formula P=(Q2 / Q1)×100%, where P is the sintering yield (%), Q2 is the mass of the finished sintered ore (particle size > 5mm), and Q1 is the total mass of the dry sintering mixture before sintering. This method for calculating the sintering yield is applicable to all embodiments and comparative examples in this invention.
[0064] In this embodiment, the liquid phase obtained after the hydrothermal reaction was analyzed, and Na was found to be present. + The concentration was approximately 2.9 g / L. This liquid phase was recycled three times in subsequent batch experiments, and the Na+ solution after recycling... + The concentration was gradually enriched to approximately 8.7 g / L. The Na₂O content and phase composition of the reconstituted product showed no significant difference from those of the freshly prepared solution, indicating that the leachate recycling technology is feasible. When the circulating liquid phase Na... +When the concentration is further enriched to 30-40 g / L, a portion of the liquid phase can be extracted for sodium and aluminum recovery, while fresh water is added to maintain concentration balance.
[0065] Example 2
[0066] Step 1: Raw material preparation; The iron-containing red mud used in this embodiment is red mud iron concentrate obtained by iron beneficiation treatment of high-iron red mud discharged during the Bayer process of an alumina plant. The chemical composition analysis results are shown in Table 4. The total iron content of this red mud iron concentrate is 44.1 wt%, the Na2O content is 6.2 wt%, and the Al2O3 content is 10.3 wt%.
[0067] Table 4. Main chemical composition of red mud iron concentrate (wt%)
[0068] X-ray diffraction analysis was performed on the above-mentioned red mud iron concentrate raw material, and the XRD pattern is shown below. Figure 4 As shown, the main phases in this raw material include: (1) hematite (Fe2O3), which is the main iron-containing phase in the raw material; (2) sodalite group minerals (Na 7.5 Al6(SiO4)6(OH) 1.5 (H2O)5 or similar composition), is one of the main carriers of Na and Al in the raw material; (3) Magnesium iron spinel (MgFe2O4). This raw material has a similar phase composition to the raw material in Example 1, but the diffraction peaks of the sodalite group minerals are stronger, consistent with its higher sodium content.
[0069] Step 2: Hydrothermal mineral phase reconstruction; Take the above-mentioned red mud iron concentrate, add calcium oxide (CaO) as a calcium-containing conditioning agent, and control the molar ratio of Ca element in the conditioning agent to the sum of Al and Si elements in the raw material, Ca / (Al+Si), to be 1.1. Add deionized water to adjust the liquid-solid ratio to 7 mL / g, and stir evenly to prepare a slurry. Put the slurry into a hydrothermal reactor and react at 170℃ for 4.0 h. After the reaction, the reaction product is subjected to solid-liquid separation. The obtained solid phase is washed three times by countercurrent washing, with a liquid-solid ratio of washing water to solid phase of 4 mL / g. After washing, dry at 105℃ for 12 h to obtain the reconstructed product.
[0070] The chemical composition of the obtained reconstructed product was analyzed, and the results are shown in Table 5.
[0071] Table 5. Main chemical composition of the reconstituted products (wt%)
[0072] As shown in Table 5, after hydrothermal mineral phase reconstruction, the Na2O content in the reconstructed product decreased from 6.21 wt% to 0.19 wt%, and the sodium removal rate reached 96.9%; the total iron content increased from 44.12 wt% to 54.9 wt%; and the CaO content reached 9.1 wt%.
[0073] Step 3: Sintering utilization; The reconstructed product obtained in Step 2 is used as an iron-containing calcium flux and added to the sintering mixture at a mass ratio of 10%. At the same time, the CaO content in the reconstructed product is converted to replace the CaO provided by quicklime in the sintering mixture in an equal amount. The basicity of the sintering mixture is kept constant by adjusting the batching. The specific proportion of the sintering mixture is shown in Table 6.
[0074] Table 6. Sintering Mix Proportion Table (dry basis, wt%)
[0075] The composition of the iron ore in Table 6 is the same as in Example 1.
[0076] Similar to Example 1, sintering tests were conducted, and the performance of the obtained sinter was tested. The drum strength was 64.2%, the yield was 76.8%, the reducibility (RI) was 87.0%, and the low-temperature reduction pulverization rate (RDI) was [not specified]. +3.15 The figure was 72.8%.
[0077] Example 3
[0078] Step 1: Raw material preparation; The iron-containing red mud used in this example is another batch of red mud iron concentrate from the high-iron red mud discharged during the Bayer process of an alumina plant, which has undergone iron beneficiation treatment. The chemical composition analysis results are shown in Table 7. The total iron content of this red mud iron concentrate is 52.0 wt%, the Na2O content is 1.6 wt%, and the Al2O3 content is 8.4 wt%. The phase composition of this raw material is similar to that of the raw material in Example 2.
[0079] Table 7. Main chemical composition of high-speed iron red mud (wt%)
[0080] Step 2: Hydrothermal mineral phase reconstruction; Take the above-mentioned high-ferrous red mud and add calcium hydroxide (Ca(OH)2) as a calcium-containing conditioning agent, controlling the molar ratio of Ca element in the conditioning agent to the sum of Al and Si elements in the raw material, Ca / (Al+Si), to be 0.8. Add deionized water to adjust the liquid-solid ratio to 10 mL / g and stir evenly to prepare a slurry. Put the slurry into a hydrothermal reactor and react at 150℃ for 5.0 h. After the reaction, the reaction product is subjected to solid-liquid separation. The obtained solid phase is washed three times by countercurrent washing, with a liquid-solid ratio of washing water to solid phase of 5 mL / g. After washing, dry at 105℃ for 12 h to obtain the reconstructed product.
[0081] The chemical composition of the obtained reconstructed product was analyzed, and the results are shown in Table 8.
[0082] Table 8. Main chemical components (wt%) of the reconstituted products
[0083] As shown in Table 8, after hydrothermal conditioning, the Na2O content in the reconstituted product decreased from 1.62 wt% to 0.13 wt%, and the sodium removal rate reached 92.0%; the total iron content increased from 52.01 wt% to 56.0 wt%; and the CaO content reached 6.6 wt%.
[0084] Step 3: Sintering utilization; The reconstructed product obtained in Step 2 is used as an iron-containing calcium flux and added to the sintering mixture at a mass ratio of 6% on a dry basis. At the same time, based on the CaO content in the reconstructed product, it replaces the CaO source provided by quicklime in the sintering mixture in an equal amount. The basicity of the sintering mixture is kept constant by adjusting the batching. The specific proportions of the sintering mixture are shown in Table 9.
[0085] Table 9. Sintering Mix Proportion Table (dry basis, wt%)
[0086] The composition of the iron ore in Table 9 is the same as in Example 1.
[0087] The sintering mixture was sintered in the same manner as in Example 1, and the performance of the resulting sinter was tested. The drum strength was 64.5%, the yield was 77.0%, the reduction ratio (RI) was 87.5%, and the low-temperature reduction pulverization rate (RDI) was [not specified]. +3.15 The figure was 73.2%.
[0088] Example 4
[0089] Step 1: Raw material preparation; The raw materials used in this example are the same as those in Example 1.
[0090] Step 2: Hydrothermal mineral phase reconstruction; Take the above-mentioned high-ferrous red mud, add calcium oxide, and control the molar ratio of Ca element in the conditioning agent to the sum of Al and Si elements in the raw material (Ca / (Al+Si)) to be 0.6. Add deionized water to adjust the liquid-solid ratio to 3 mL / g, and stir evenly to prepare a slurry. Put the slurry into a hydrothermal reactor and react at 150℃ for 1 h. After the reaction is completed, wash and dry as in Example 1 to obtain the reconstructed product.
[0091] The chemical composition of the obtained reconstructed product was analyzed, and the results are shown in Table 10.
[0092] Table 10. Main chemical composition of the reconstructed products (wt%)
[0093] As shown in Table 10, after hydrothermal mineral phase reconstruction, the Na2O content in the reconstructed product decreased from 3.52 wt% to 0.5 wt%, and the sodium removal rate reached 85.8%; the total iron content increased from 40.12 wt% to 50.2 wt%; and the CaO content reached 5.3 wt%.
[0094] Step 3: Sintering utilization; The reconstructed product obtained in Step 2 is used as an iron-containing calcium flux and added to the sintering mixture at a mass ratio of 5%. At the same time, the CaO content in the reconstructed product is converted to replace the CaO provided by quicklime in the sintering mixture in an equal amount. The basicity of the sintering mixture is kept constant by adjusting the batching. The specific proportion of the sintering mixture is shown in Table 11.
[0095] Table 11 Sintering Mix Proportion Table (dry basis, wt%)
[0096] The composition of the iron ore in Table 11 is the same as in Example 1.
[0097] The basicity (CaO / SiO2) of the sintering mixture was controlled at 2.0, and the moisture content was 8.0%. The sintering mixture was sintered in the same manner as in Example 1. The resulting sinter was tested for performance: drum strength was 62.5%, yield was 74.8%, reduction ratio (RI) was 85.2%, and low-temperature reduction pulverization rate (RDI) was [not specified]. +3.15 The figure was 71.0%.
[0098] Because the Ca / (Al+Si) molar ratio is at the lower limit, the reaction temperature is low, and the reaction time is short, the sodium removal rate is at the lower limit of this invention, the residual sodium and active aluminum are slightly high, and the sintered ore performance is slightly lower than that of Example 1.
[0099] Example 5
[0100] Step 1: Raw material preparation; The raw materials used in this example are the same as those in Example 1.
[0101] Step 2: Hydrothermal mineral phase reconstruction; Take the above-mentioned high-ferrous red mud, add calcium oxide, and control the molar ratio of Ca element in the conditioning agent to the sum of Al and Si elements in the raw material (Ca / (Al+Si)) to be 0.9. Add deionized water to adjust the liquid-solid ratio to 9 mL / g, and stir evenly to prepare a slurry. Put the slurry into a hydrothermal reactor and react at 185℃ for 3.5 h. After the reaction is completed, wash and dry as in Example 1 to obtain the reconstructed product.
[0102] The chemical composition of the obtained reconstructed product was analyzed, and the results are shown in Table 12.
[0103] Table 12 Main chemical composition of the reconstructed products (wt%)
[0104] As shown in Table 12, after hydrothermal mineral phase reconstruction, the Na2O content in the reconstructed product decreased from 3.52 wt% to 0.20 wt%, and the sodium removal rate reached 94.3%; the total iron content increased from 40.12 wt% to 52.3 wt%; and the CaO content reached 9.0 wt%.
[0105] Step 3: Sintering utilization; The reconstructed product obtained in Step 2 is used as an iron-containing calcium flux and added to the sintering mixture at a mass ratio of 9%. At the same time, the CaO content in the reconstructed product is converted to replace the CaO provided by quicklime in the sintering mixture in an equal amount. The basicity of the sintering mixture is kept constant by adjusting the batching. The specific proportion of the sintering mixture is shown in Table 13.
[0106] Table 13 Sintering Mix Proportion Table (dry basis, wt%)
[0107] The composition of the iron ore in Table 13 is the same as in Example 1.
[0108] The basicity (CaO / SiO2) of the sintering mixture was controlled at 2.0, and the moisture content was 7.2%. Sintering tests were conducted according to the following parameters: the sintering mixture was loaded into a sintering cup, the ignition temperature was 1120℃, the ignition time was 90s, the negative pressure was 14kPa, the highest temperature of the combustion zone in the material layer during sintering was approximately 1290℃, and the material was allowed to cool naturally after sintering. The performance of the obtained sinter was tested: drum strength was 65.3%, yield was 78.5%, reducibility (RI) was 88.6%, and low-temperature reduction pulverization rate (RDI) was [not specified]. +3.15 The figure was 74.2%.
[0109] Comparative Example 1
[0110] Using the same raw materials as in Example 1, the hydrothermal treatment conditions were changed: the molar ratio of Ca element in the conditioning agent to the sum of Al and Si elements in the raw materials, Ca / (Al+Si), was 1.5; the hydrothermal temperature was 220℃; the reaction time was 3h; and the other conditions were the same as in Example 1.
[0111] The obtained product contained 0.19 wt% Na₂O and 50.8 wt% TFe. XRD analysis showed that the peaks of the natronite group minerals disappeared in the product, but a large number of diffraction peaks of free calcium oxide (CaO) appeared, and the diffraction peak intensity of the calcium aluminum silicate phase was weak. Weak characteristic peaks of the andradite-type phase were also detected. This product was added to the sintering mixture at a ratio of 8 wt%, replacing limestone with CaO equivalent. Sintering results showed that the drum strength decreased to 61.0%, and the yield decreased to 73.5%. An excessively high Ca / (Al+Si) molar ratio resulted in residual free CaO in the product and promoted the entry of some Ca, Fe, and Al into the andradite-type high-melting-point phase. Free CaO underwent exothermic digestion during the granulation process of the sintering mixture, affecting the granulation effect, while the high-melting-point phase reduced the effective release of calcium source in the SFCA generation temperature range. Simultaneously, excess CaO easily reacted with aluminum components during sintering to form high-melting-point calcium aluminate, consuming the CaO used to generate the calcium ferrite binder phase.
[0112] Comparative Example 2
[0113] Using the same raw materials as in Example 1, the hydrothermal treatment conditions were changed: the molar ratio of Ca element in the conditioning agent to the sum of Al and Si elements in the raw materials, Ca / (Al+Si), was 0.5; the hydrothermal temperature was 180℃; the reaction time was 3h; and the other conditions were the same as in Example 1.
[0114] The obtained product had a Na₂O content of 0.71 wt%, a sodium removal rate of 79.8%, a TFe content of 49.8 wt%, and an Al₂O₃ content of 9.3%. XRD analysis showed that the diffraction peak intensity of the sodalite group minerals in the product was significantly weakened but not completely disappeared, and the diffraction peak intensity of the calcium aluminum silicate phase was weak, while the characteristic peak of boehmite could still be detected. This product was added to the sintering mixture at a ratio of 8%, replacing limestone with CaO equivalent. Sintering results showed that the drum strength decreased to 61.5%, and the yield decreased to 73.8%. When the Ca / (Al+Si) molar ratio was too low, the calcium source was insufficient to fully react with the aluminum and silicon components to form the target calcium aluminum silicate phase, resulting in incomplete sodium removal and a large amount of residual active aluminum-containing phase. The residual active aluminum competed with CaO during the sintering process, consuming the CaO used to form the calcium ferrite binder phase, while the residual sodium still posed a potential risk to blast furnace operation.
[0115] Comparative Example 3
[0116] Using the same raw materials as in Example 2, the hydrothermal treatment conditions were changed: the molar ratio of Ca element in the conditioning agent to the sum of Al and Si elements in the raw materials, Ca / (Al+Si), was 1.1; the hydrothermal temperature was 120℃; the reaction time was 4h; and the other conditions were the same as in Example 2.
[0117] The obtained product had a Na₂O content of 1.28 wt%, with a sodium removal rate of only 79.4%. XRD analysis showed that residual diffraction peaks of sodalite group minerals remained in the product, indicating that sodalite decomposition was incomplete under low-temperature conditions. Adding this product at a ratio of 10 wt% to the sintering mixture reduced the sinter drum strength to 61.8% and the yield to 74.0%. At excessively low temperatures, the hydrothermal reaction driving force is insufficient, resulting in incomplete decomposition of sodalite group minerals, low sodium removal rate, and residual sodium volatilizing and circulating during sintering, which deteriorates the permeability of the bed and leads to a decline in the quality of the sinter.
[0118] Comparative Example 4
[0119] Using the same raw materials as in Example 1, without any hydrothermal conditioning treatment, the original red mud was directly added to the sintering mixture at a mass ratio of 8 wt%, and the proportioning was adjusted in the same way to maintain consistent alkalinity. The remaining conditions were the same as in Example 1.
[0120] Sintering tests were conducted in the same manner as in Example 1. The sintering results showed that the drum strength decreased to 58.5%, the yield decreased to 69.0%, the reduction degree decreased to 78.5%, and the low-temperature reduction pulverization rate (RDI) decreased. +3.15 The permeability of the raw red mud deteriorated to 65.0%. Sodium in the original red mud volatilized and accumulated in large quantities during the sintering process, which worsened the permeability of the material layer. The active aluminum-containing phase in the original red mud released active Al2O3 at the high temperature of sintering, which increased the viscosity of the liquid phase, hindered the formation of calcium ferrite, and led to a decrease in the strength of the sinter and a deterioration in its reducibility.
[0121] Comparative Example 5
[0122] Using the same reconstructed product as in Example 5, the difference was that the moisture content of the sintering mix was increased to 10.0%, otherwise the same as in Example 5. Sintering results showed: drum strength 61.5%, yield 71.0%, reduction degree 84.5%, and low-temperature reduction pulverization rate (RDI). +3.15 The moisture content was 68.0%. Excessive moisture content in the sintering mixture (above 8.0%) will deteriorate the sintering quality.
[0123] Comparative Example 6
[0124] The same reconstructed product as in Example 5 was used, except that the sintering ignition temperature was lowered to 950°C; otherwise, the process was the same as in Example 5. Sintering results showed: drum strength 60.8%, yield 70.5%, reduction degree 83.5%, and low-temperature reduction pulverization rate (RDI). +3.15 The percentage was 67.5%. Poor surface sintering was caused by an excessively low sintering ignition temperature (below 1050℃).
[0125] Comparative Example 7
[0126] Using the same reconstructed product as in Example 5, the difference was in step 3: sintering utilization. The reconstructed product obtained in step 2 was used as an iron-calcareous flux and added to the sintering mixture at a mass ratio of 25%, with the rest remaining the same as in Example 5. Sintering results showed that the drum strength decreased to 60.2%, the yield decreased to 70.8%, the reduction ratio (RI) decreased to 83.8%, and the low-temperature reduction pulverization rate (RDI) decreased. +3.15 The percentage of reconstituted products decreased to 67.0%. The results indicate that while a high proportion of reconstituted products can further increase the amount of red mud absorbed, it also significantly increases the fine particle content and the input of components such as Al2O3 and CaO in the mixture, leading to poorer granulation and bed permeability. Simultaneously, excessive calcium aluminum silicate phases increase the viscosity of the sintering liquid phase and dilute the proportion of conventional iron ore, which is detrimental to iron mineral assimilation and the uniform formation of the SFCA binder phase. Therefore, the proportion of reconstituted products in the sintering mixture should be controlled between 5 and 20 wt%.
[0127] Comparative Example 8
[0128] All other conditions were identical to those in Example 5, except that the ignition temperature was 1250°C. The sintering results were: drum strength 61.9%, yield 72.3%, reduction ratio (RI) 84.7%, and low-temperature reduction pulverization rate (RDI). +3.15 The percentage was 68.6%. This indicates that excessively high ignition temperatures can lead to over-melting of the surface sinter, reduced permeability of the material layer, uneven distribution of the liquid phase, and may cause excessive local bonding and deterioration of the mineral structure, thereby reducing the strength and metallurgical properties of the sinter.
[0129] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. An iron-containing flux prepared from red mud, characterized in that: The iron-containing flux is prepared by the following steps; Step 1: Raw material preparation: Select iron-containing red mud or red mud iron concentrate as raw materials; Step 2: Hydrothermal mineral phase reconstruction: The raw material is mixed with a calcium-containing conditioning agent and water to form a slurry. A mineral phase reconstruction reaction is carried out under hydrothermal conditions. The calcium-containing conditioning agent is calcium oxide and / or calcium hydroxide. The hydrothermal treatment conditions are: temperature 150–200℃, time 1–7 h, liquid-to-solid ratio 3–12 mL / g, and the molar ratio of Ca element in the calcium-containing conditioning agent to the sum of Al and Si elements in the raw material (Ca / (Al+Si)) is 0.6–1.
1. After the reaction, solid-liquid separation is performed. The obtained solid phase is then washed using a countercurrent washing method. The liquid-to-solid ratio of the washing liquid to the solid phase is 3–10 mL / g, and the washing is performed 2–3 times. After hydrothermal mineral phase reconstruction and washing, the removal rate of sodium in the raw material is not less than 85%, and the removal rate of aluminum is not less than 40%. The reconstructed product is the iron-containing flux.
2. The iron-containing flux prepared from red mud according to claim 1, characterized in that: The Na2O content in the iron-containing flux is not higher than 0.5 wt%. The iron-containing flux contains not less than 50 wt% TFe and 5-12 wt% CaO. The iron-containing flux contains 3-8 wt% Al2O3. The X-ray diffraction pattern of the iron-containing flux shows characteristic diffraction peaks of calcium aluminum silicate crystal phase belonging to the CaO-Al2O3-SiO2 system, but no characteristic diffraction peaks of sodalite group minerals, no characteristic diffraction peaks of boehmite, and no characteristic diffraction peaks of aluminum hydroxide phase.
3. The iron-containing flux prepared from red mud according to claim 1, characterized in that: The hydrothermal treatment in step 2 is performed at a temperature of 170–190°C for 2–5 hours, with a liquid-to-solid ratio of 5–10 mL / g.
4. The iron-containing flux prepared from red mud according to claim 1, characterized in that: When calcium oxide is selected as the calcium-containing conditioning agent, the hydrothermal treatment temperature is 170-190℃, the time is 2-5h, the liquid-to-solid ratio is 5-9mL / g, and the molar ratio of Ca element in the calcium-containing conditioning agent to the sum of Al and Si elements in the raw material, Ca / (Al+Si), is 0.8-1.
0. When calcium hydroxide is selected as the calcium-containing conditioning agent, the hydrothermal treatment temperature is 170-190℃, the time is 3-6h, the liquid-to-solid ratio is 8-10mL / g, and the molar ratio of Ca element in the calcium-containing conditioning agent to the sum of Al and Si elements in the raw material, Ca / (Al+Si), is 0.8-1.
0.
5. The iron-containing flux prepared from red mud according to claim 1, characterized in that: The raw materials mentioned in step 1 have a TFe content of 30~55wt%, a Na2O content of greater than or equal to 1wt%, an Al2O3 content of 4~20wt%, and a SiO2 content of 0.5~20wt%.
6. The application of an iron-containing flux prepared from red mud as described in any one of claims 1-5, characterized in that: The obtained iron-containing flux is added to the ironmaking raw materials as an iron-containing calcium flux and mixed evenly to obtain a sintering mixture. The proportion of iron-containing flux added to the sintering mixture is 5-20 wt%; the moisture content is 6.5-8.0 wt%; the CaO content in the iron-containing flux is converted to an equal amount to replace the CaO provided by limestone and / or quicklime in the sintering mixture, and the basicity of the sintering mixture is kept constant in the range of 1.8-2.2 by adjusting the batching. Ironmaking furnace charge is prepared by sintering process. After the sintering mixture is added to the sintering furnace, it is ignited at 1050-1180℃ and then sintered. During sintering, the negative pressure of the exhaust fan is controlled at 8-15 kPa and the sintering temperature is 1250-1350℃.
7. The application of the iron-containing flux prepared from red mud as a raw material according to claim 6, characterized in that: The sintering mixture consists of iron ore, iron-containing flux, limestone, quicklime, dolomite, fuel, and recycled ore; on a dry basis by mass percentage, the iron ore is 50-75%, the iron-containing flux is 5-12%, the limestone is 2-10%, the quicklime is 0-10%, the dolomite is 0-8%, the fuel is 3-8%, and the recycled ore is 5-15%; the sum of the contents of all components is 100%; the fuel is coke powder.
8. The application of the iron-containing flux prepared from red mud according to claim 6, characterized in that: On a dry basis by mass percentage, the iron ore contains 55–68 wt% TFe, 2–10 wt% SiO2, 0.5–5 wt% Al2O3, 0–8 wt% CaO, 0–5 wt% MgO, 0–10 wt% FeO, 0–12 wt% loss on ignition, no more than 0.15 wt% S, and no more than 0.20 wt% P.
9. The application of the iron-containing flux prepared from red mud according to claim 6, characterized in that: Returned ore is the portion of sinter that is crushed and screened and then returned to the sintering batching system. On a dry basis, the returned ore contains 50–62 wt% TFe, 5–15 wt% FeO, 4–9 wt% SiO2, 1–5 wt% Al2O3, 8–16 wt% CaO, 1–5 wt% MgO, 0–5 wt% loss on ignition, no more than 0.15 wt% S, and no more than 0.20 wt% P. The basicity of the returned ore (CaO / SiO2) is 1.6–2.5, and the particle size is less than 5 mm.
Citation Information
Patent Citations
Low-temperature low-pressure hydro chemical method for recovering aluminum oxide and sodium oxide from red mud
CN101538058A
Method for preparing tobermorite type thermal-insulating and fireproofing material from sintered red mud
CN109020459A
Method for preparing 4A zeolite from MSWI fly ash and red mud by hydrothermal method
CN113716583A
Method for comprehensively recycling multiple components of red mud
CN116040666A
Method for recycling alumina and sodium oxide from bayer process red mud
CN103030160A